2015
DOI: 10.1051/0004-6361/201425531
|View full text |Cite
|
Sign up to set email alerts
|

Radial velocities and metallicities from infrared Ca ii triplet spectroscopy of open clusters

Abstract: Context. Open clusters are key to studying the formation and evolution of the Galactic disc. However, there is a deficiency of radial velocity and chemical abundance determinations for open clusters in the literature. Aims. We intend to increase the number of determinations of radial velocities and metallicities from spectroscopy for open clusters. Methods. We acquired medium-resolution spectra (R ∼ 8000) in the infrared region Ca ii triplet lines (∼8500 Å) for several stars in five open clusters with the long… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 50 publications
(87 reference statements)
2
13
1
Order By: Relevance
“…On average, the radial velocities derived here are 15 km s −1 larger than those derived by Carrera et al (2015). A problem with the wavelength calibration of the King 1 spectra analysed by Carrera et al (2015) may explain this discrepancy.…”
Section: Dimension First Lastcontrasting
confidence: 71%
See 2 more Smart Citations
“…On average, the radial velocities derived here are 15 km s −1 larger than those derived by Carrera et al (2015). A problem with the wavelength calibration of the King 1 spectra analysed by Carrera et al (2015) may explain this discrepancy.…”
Section: Dimension First Lastcontrasting
confidence: 71%
“…However, the relations used to derive the stellar metallicities were obtained only for red giant branch stars. Carrera et al (2015) demonstrated that the maximum difference in ΣCa between red clump and red giant branch stars is ∼0.16Å. This implies that the metallicity of a red clump star derived with the red giant branch relationships may be over-estimated by a maximum of ∼0.07 dex, independent of the luminosity indicator used.…”
Section: Metallicity Determinationmentioning
confidence: 92%
See 1 more Smart Citation
“…Friel et al (2002) presented an update of previous investigations by using spectrophotometric indices to derive metallicities of 39 open clusters. Furthermore, from the studies by Carrera et al (2007), Carrera (2012), Carrera et al (2015), and Warren & Cole (2009), we compiled metallicity estimates of 28 open clusters. These authors made use of reduced equivalent widths (W ) of the Ca  triplet lines, which show a linear relation with metallicity.…”
Section: Photometric Metallicitiesmentioning
confidence: 99%
“…Again, it lies on the same isochrone as B-type confirmed spectroscopic members (figs 9 and 10 in N12). W2249 is 74 from the centre of NGC 6603; the seven targets -including W2249for which radial velocities supported cluster membership (Carrera et al 2015) lie within 5 of the centre.…”
Section: Introductionmentioning
confidence: 99%